2014
DOI: 10.1128/mcb.00711-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Role of Phosphorylation of Cryptochrome 2 in the Mouse Circadian Clock

Abstract: The circadian clock is finely regulated by posttranslational modifications of clock components. Mouse CRY2, a critical player in the mammalian clock, is phosphorylated at Ser557 for proteasome-mediated degradation, but its in vivo role in circadian organization was not revealed. Here, we generated CRY2(S557A) mutant mice, in which Ser557 phosphorylation is specifically abolished. The mutation lengthened free-running periods of the behavioral rhythms and PER2::LUC bioluminescence rhythms of cultured liver. In l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…The stability of CRY1 and CRY2 significantly affects the circadian period at molecular and behavioral levels (Godinho et al, 2007; Hirano et al, 2014; 2016a; Ode et al, 2016; Siepka et al, 2007). Additionally, the FASP mouse model expressing A260T-CRY2 protein exhibits shorter circadian period of both behavioral rhythms and cellular rhythms in peripheral tissues (Hirano et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…The stability of CRY1 and CRY2 significantly affects the circadian period at molecular and behavioral levels (Godinho et al, 2007; Hirano et al, 2014; 2016a; Ode et al, 2016; Siepka et al, 2007). Additionally, the FASP mouse model expressing A260T-CRY2 protein exhibits shorter circadian period of both behavioral rhythms and cellular rhythms in peripheral tissues (Hirano et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that dysregulation of CRY stabilities caused abnormal periodicity in mouse behavioral rhythms and gene expression rhythms [ 12 , 14 , 15 , 17 , 31 , 32 ]. For example, knockdown or knockout of Fbxl3 lengthened the circadian period [ 15 , 16 ], whereas knockdown or mutation of Fbxl21 shortened the period [ 15 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…This sequential phosphorylation recruits an unknown E3 ligase, thereby leading to CRY2 degradation 70 . Mutation at the priming site (S557A) leads to decreased CRY2 turnover and a lengthened circadian period in mice 72 . However, phosphorylation at Ser588 in the C-terminal region of CRY1 prevents the FBXL3-CRY1 interaction and consequently increases CRY1 stability 73 .…”
Section: Q9 Q9mentioning
confidence: 99%